An obligation to care for seriously ill children in their homes: A qualitative study of community nurses' perceptions. (December 2017) - Grimheden, Sofia; Lindqvist, Gunilla; Bylund-Grenklo, Tove; Sandgren, Anna
When children are seriously ill, being able to be cared for at home with the family is valuable, but community nurses are often not trained to care for children. The aim of this study was therefore to describe community nurses' perceptions of caring for seriously ill children at home. A content analysis was conducted of 11 semi-structured interviews with nurses. One theme, obligation to care, was found, followed by three categories: making an impact, feeling confident, and emotional processing . In conclusion, we found collaboration with paediatric staff in the hospital is important for community nurses in order to gain confidence, which would optimise care at home for seriously ill children and their families.